Temperature measurement using infrared thermometry within semi-transparent media. Issue 6 (2nd November 2019) - Sielaff, A.; Gowik, M.; Völzel, C.; Rosengarten, G.; Rajic, N.; Stephan, P.
ABSTRACT: Infrared thermometry is a widely used technique for contactless temperature measurement, which is often conducted through semi-transparent media. In the present work, influences on the measurement results stemming from semi-transparent media and from the optical characteristics of the measurement setup are discussed. Results of two experimental setups, containing low, medium, and high transmission media are presented and compared to calculated data using a one-dimensional analytical approach and a three-dimensional ray-tracing algorithm. It is shown through modeling and experiments that the surroundings and, in particular, the (semi)transparent materials within the optical path are critical for accurate temperature measurements.